Soil initial bacterial diversity and nutrient availability determine the rate of xenobiotic biodegradation. Issue 1 (24th October 2021) - Jayaramaiah, Ramesha H.; Egidi, Eleonora; Macdonald, Catriona A.; Wang, Jun‐Tao; Jeffries, Thomas C.; Megharaj, Mallavarapu; Singh, Brajesh K.
Summary: Understanding the relative importance of soil microbial diversity, plants and nutrient management is crucial to implement an effective bioremediation approach to xenobiotics‐contaminated soils. To date, knowledge on the interactive effects of soil microbiome, plant and nutrient supply on influencing biodegradation potential of soils remains limited. In this study, we evaluated the individual and interactive effects of soil initial bacterial diversity, nutrient amendments (organic and inorganic) and plant presence on the biodegradation rate of pyrene, a polycyclic aromatic hydrocarbon. Initial bacterial diversity had a strong positive impact on soil biodegradation potential, with soil harbouring higher bacterial diversity showing ~ 2 times higher degradation rates than soils with lower bacterial diversity. Both organic and inorganic nutrient amendments consistently improved the degradation rate in lower diversity soils and had negative (inorganic) to neutral (organic) effect in higher diversity soils. Interestingly, plant presence/type did not show any significant effect on the degradation rate in most of the treatments. Structural equation modelling demonstrated that initial bacterial diversity had a prominent role in driving pyrene biodegradation rates. We provide novel evidence that suggests that soil initial microbial diversity, and nutrient amendments should be explicitly considered in the design and employment of bioremediation management strategies for restoring natural habitats disturbed by organic pollutants. Abstract : We provide novel evidence that suggests that soil initial microbial diversity and nutrient availability are main predictors of xenobiotic degradation. These variables should be explicitly considered in the design and employment of bioremediation management strategies for restoring natural habitats disturbed by organic pollutants.